PERANAN GURU PPKn DALAM MENANAMKAN KARAKTER TOLERANSI PADA SISWA DI SMP NEGERI 1 PEKANBARU - Fauziah Fauziah; Ahmad Eddison; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Civic Education Teachers have a considerable role and responsibility to foster student attitudes and behavior, one of which includes an attitude of tolerance towards students. Because civic education is a subject that focuses on the formation of citizens who understand and can carry out the rights and obligations to become intelligent, skilled and characterized Indonesian citizens mandated by Pancasila and Undang-Undang 1945. The purpose of this study is to find out how the role of PPKn teacher’s in embedding character tolerance in students in SMP Negeri 1 Pekanbaru. To find out how the tolerance character of student in SMP Negeri 1 Pekanbaru. To find out how there is an influence of the role of PPKn teacher’s in embedding character tolerance in student in SMP Negeri 1 Pekanbaru. The subjects in this study were students of SMP Negeri 1 Pekanbaru with a total of VII grade students, there are 5 classes with 163 students, VIII classes there are 6 classes with 234 students and Class IX there are 7 classes with a total of 291 students. The sample in this study was taken using a proportional sampling technique with 10% of subjects. The technique of data collection is done through observation, questionnaire, interview and documentation. In analyzing data using quantitative descriptive techniques with statistical tests. The results of this study indicate that the role of the PPKn teacher in instilling tolerance character is at a very good level. There is a significant influence in this study because it is known that the results of a simple linear regression between variables X and Y, obtained Fcount of 4.273 and Ftable of 3.99 indicates Fcount> Ftable, so that Ho is rejected and Ha is accepted. The influence is low because the results obtained by 24.8%.Key Words: The Role, PPKn Teachers, Tolerance Character.